2002
DOI: 10.1103/physrevlett.89.025703
|View full text |Cite
|
Sign up to set email alerts
|

Boundary between Long-Range and Short-Range Critical Behavior in Systems with Algebraic Interactions

Abstract: We investigate phase transitions of two-dimensional Ising models with power-law interactions, using an efficient Monte Carlo algorithm. For slow decay, the transition is of the mean-field type; for fast decay, it belongs to the short-range Ising universality class. We focus on the intermediate range, where the critical exponents depend continuously on the power law. We find that the boundary with short-range critical behavior occurs for interactions depending on distance r as r 215͞4 . This answers a long-stan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
146
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(159 citation statements)
references
References 24 publications
11
146
2
Order By: Relevance
“…In the meantime, the first numerical study of the Ising model with the long-range interaction was reported by Luijten and Blöte [10]. By means of the cluster-algorithm Monte Carlo method, they calculated the exponent η for d = 2 as a function of σ, concluding that η = 2 − σ up to 2 − σ = η sr and η = η sr = 1/4 for larger σ.…”
Section: Summary Of Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, the first numerical study of the Ising model with the long-range interaction was reported by Luijten and Blöte [10]. By means of the cluster-algorithm Monte Carlo method, they calculated the exponent η for d = 2 as a function of σ, concluding that η = 2 − σ up to 2 − σ = η sr and η = η sr = 1/4 for larger σ.…”
Section: Summary Of Previous Workmentioning
confidence: 99%
“…For the d-dimensional system with the long-range interaction, this continuous change of the critical exponents between the short-range and the meanfield universalities can be interpreted as the continuous change of the effective dimension between d and the upper critical dimension of the corresponding short range model. Although a number of theoretical and numerical studies [2,3,[9][10][11][12][13][14][15][16] have been conducted in order to interpret the intermediate regime as non-integral dimensions, precise identification between the decay exponent, σ, and the effective dimension has not been well established so far, in spite of the simple form of the Hamiltonian (1).…”
Section: Introductionmentioning
confidence: 99%
“…This crossover has recently been reexamined numerically in d = 2 in Ref. [33]. Fluids are governed by dispersion forces.…”
Section: A Bulk Systemsmentioning
confidence: 99%
“…at the critical point [24]. Since according to scaling relations, γ/ν = 2 − η and η = 2 − σ + δη for a LR system, the scaling of S will be used to evaluate the correction δη to the power law decay of the correlation functions at criticality.…”
Section: Observablesmentioning
confidence: 99%